IBUPROFEN IN COMPLEX TREATMENT OF FEVER IN CHILDREN - А.А. Alexeeva; Е.А. Vishneva; Yu.G. Levina; R.М. Torshkhoeva ("Paediatrician" Publishers LLC, 2011)
Pain and fever are one of the most frequent conditions in pediatric practice. Frequent occurrence of fever accompanied by a pain syndrome stipulates combined antipyretic and analgesic medications. This article contains information upon ibuprofen use («Nurofen for children») in pediatric patients as an antipyretic and analgesic medication to be used as part of complex treatment of acute respiratory infections.Key words: fewer, children, ibuprofen. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 137-140)